Roman Catholic revivalism: a study of the area that became the diocese of Middlesbrough 1779-1992 - Turnham, Margaret H. (2012)
This thesis seeks to provide a grassroots study of the diocese of Middlesbrough (1779-1992), in order to contribute to the history of the English Catholic community since it emerged from the Penal Times. Secondly, it is an examination of the manifestation of revivalism and renewal in Catholic devotional practice. The geographical extent of the study covers an area of Yorkshire with a strong recusant history, and that period has been well-served in Catholic historiography. However, writing on the period following the easing of the Penal Laws on Catholics and into the nineteenth and twentieth centuries is remarkable for the paucity of references to the diocese and the area that it covers. Therefore this study sheds light upon a particular Catholic community that has been largely invisible to historians. Although the Catholic community itself might appear to be invisible, the devotional practice within it offers many insights, such as the extent to which the social culture influenced the practice of faith. Therefore it teases out and examines the changing nature of devotional practice, and compares it to aspects of Evangelical revivalism that provided the surrounding religious culture. It also examines the influences that came to bear upon the community itself, assessing their importance in the revival and renewal of faith of the people within it. By examining the history of Catholic devotional practice in this area of Yorkshire, it comes to the conclusion that revivalism and renewal are integral elements in Catholic devotion and as a result Catholics and Evangelicals have more in common with each other than their adherents have been ready to acknowledge.